A feeding obturator appliance in infants with isolated cleft palate: A case series - Kamaljit Kaur; Aditi Kapur; Bhavita Wadhwa Soni; Manojkumar Ashok Jaiswal (Wolters Kluwer Medknow Publications, 2023)
Feeding a child with cleft lip with or without cleft palate (CL/P) is a matter of concern for both the parents and the physician. Early knowledge about various available options and timely intervention can overcome undue anxiety in parents of children with CL/P. A feeding obturator separates the oral cavity from the nasal cavity and is one of the means to aid in adequate nutrition to the affected child. The present article describes two cases of successful use of a feeding obturator in infants with an isolated CL/P.